(untitled) (European Journal of Teaching and Education, 2025)
Purpose: The contemporary learning environment is shifting towards innovative, learner-centered pedagogical approaches, such as the flipped classroom, that foster critical and engaged thinkers. This model replaces traditional lectures with pre-recorded online content students peruse before the class to facilitate interactive discussions and collaborative activities during face-to-face sessions. Methodology: This study investigated the impact of the flipped classroom on critical thinking and student engagement among six female sociology students at a Trinidadian tertiary institute over one semester. Data was gathered using an action research design utilizing mixed methods collected through classroom observations, student assessments, and student feedback. Findings: Post-intervention results demonstrated increased student engagement but no significant improvement in task completion rates. The study also noted a moderate increase in critical thinking skills reflected in students’ written assessments but stronger demonstrations during interactive class discussions and group activities in the flipped setting. Implications: While the small sample size and subjective nature of this action research limit the generalizability of the findings, the study offers valuable insights into the unique learning context of the participants and highlights the potential benefits of using the flipped classroom model in Trinidadian classrooms.